2023
DOI: 10.1186/s12891-023-06264-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of apolipoprotein A1 with osteoporosis: a cross-sectional study

Abstract: Summary Higher levels of apolipoprotein A1 (ApoA1) were associated with higher risk of osteoporosis, which supports the argument that lipid metabolism is involved in bone metabolism. Background Although the current evidence shows that lipid metabolism and osteoporosis are closely related to cardiovascular disease, the association between ApoA1 and osteoporosis is still unknown. Therefore, the purpose of this study was to explore the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Moreover, another cross-sectional study also found that higher triglyceride and total cholesterol levels were associated with a greater prevalence of osteoporosis [ 26 ]. It was also shown that participants with higher apolipoprotein A1 levels had a 71.2% greater risk of developing osteoporosis than those with lower apolipoprotein A1 levels, and for each one-unit increase in apolipoprotein A1, the risk was 1.29 times greater [ 27 ]. Moreover, two previous studies demonstrated that the renin-angiotensin system (RAS) plays a significant role in osteoporosis, where the activation of the local RAS in bone tissue can lead to increased bone resorption, thereby triggering osteoporosis, and the use of RAS inhibitors can significantly reduce the incidence of osteoporosis and osteoporotic fractures [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another cross-sectional study also found that higher triglyceride and total cholesterol levels were associated with a greater prevalence of osteoporosis [ 26 ]. It was also shown that participants with higher apolipoprotein A1 levels had a 71.2% greater risk of developing osteoporosis than those with lower apolipoprotein A1 levels, and for each one-unit increase in apolipoprotein A1, the risk was 1.29 times greater [ 27 ]. Moreover, two previous studies demonstrated that the renin-angiotensin system (RAS) plays a significant role in osteoporosis, where the activation of the local RAS in bone tissue can lead to increased bone resorption, thereby triggering osteoporosis, and the use of RAS inhibitors can significantly reduce the incidence of osteoporosis and osteoporotic fractures [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids play a vital role in various physiological processes, including bone metabolism. Several studies have underscored the influence of lipids on bone health [ 5 ], indicating a potential association between specific lipid components, such as apolipoprotein B (apo B), and BMD [ 6 ]. Apo B, a primary component of atherogenic lipoproteins with two major isoforms: apo B48 and apo B100 [ 7 ], is implicated in numerous metabolic processes besides cholesterol transport.…”
Section: Introductionmentioning
confidence: 99%